Electric Vehicle as an Energy Storage for Grid Connected Solar Power System - E. Sheeba Percis; Manivannan S; Nalini A (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In the past few years the growing demand for electricity and serious concern for the environment have given rise to the growth of sustainable sources like wind, solar, tidal, biomass etc. The technological advancement in power electronics has led to the extensive usage of solar power. Solar power output varies with the weather conditions and under shading conditions. With the increasing concerns of the impacts of the high penetration of Photovoltaic (PV) systems, a technical study about their effects on the power quality of the utility grid is required. This paper investigates the functioning of a grid-tied PV system along with maximum power point tracking (MPPT) algorithm. The effects of varying atmospheric conditions like solar irradiance and temperature are also taken into account. It is proposed in this work that an Electric Vehicle (EV) can be used as an energy storage to stabilize the power supplied to the grid from the photovoltaic resources. A coordinated control is necessary for the EV to obtain desired outcome. The modeling of the PV and EV system is carried out in PSCAD and the proposed idea is verified through simulation results utilizing real field data for solar irradiance and temperature.